Activity proposals to improve children’s climate literacy and environmental literacy - Ramos, Ricardo (2024)
With the climate crisis, schools have a fundamental role to enrich children’s climate literacy, which should begin in their early years and continue for life. Developing activities in the classroom can be an excellent way of bringing this about. This work is part of a larger research project, during which a previous study was carried out with 245 children aged 9 to 13, in which we identified some limitations in their knowledge about climate change. Based on these results, we decided to present some proposals for activities that could help improve these children’s climate literacy. The study we conducted was of an exploratory character, and the main objective was to understand the impact of applying a set of activities to 54 children. The objectives of this work were to increase the climate literacy of the children involved—more specifically, to evaluate the impact of implementing three activities related to climate change and identify the knowledge about the cases and consequences of climate change that were acquired by the children involved. To collect the data, we used a focus group technique and content analysis to process it. The results revealed that the children acquired a better understanding of the problem of climate change—in particular, the causes and consequences of it and of the concept of the ecological footprint—as well as motivation to contribute to mitigating the problem. We conclude that the activities proposed could contribute to improving climate literacy, as well as stimulate children’s curiosity and proactivity so that they become citizens capable of exercising their active citizenship.